Wages, employment, and capital in capitalist and worker-owned firms - John H. Pencavel; Luigi Pistaferri; Fabiano Schivardi (Institute for the Study of Labor (IZA), 2006)
Differences in wages, employment, and capital between worker-owned and capitalist enterprises are computed from a matched employer-worker panel data set from Italy, the market economy with the greatest incidence of worker-owned and worker-managed firms. These differences are related to orthodox models of the capitalist firm and worker co-op. The estimates of the wage, employment, and capital equations largely corroborate the implications of the behavioral models of the two types of enterprise. Co-op wages are about 14 percent lower on average and they are more volatile (and employment less volatile) than those in capitalist enterprises. Given the breadth of the data set analyzed, the results can claim to constitute general findings about capitalist and co-op enterprises.
Keywords: J54; D21; L21; 330; worker-owned firms; capitalist firms; wages; employment; capital; Arbeiterselbstverwaltung; Lohn; Beschäftigung; Volatilität; Unternehmen; Kapital; Italien